Al (110) surface oxide thermal stability in ultrahigh vacuum. (4th September 2013) - Cai, Minzhen; Outlaw, Ronald A.; Butler, Sue M.; Miller, John R.
<x xml:space="preserve">Abstract</x> This research characterizes the stability of the Al2O3 surface oxide on Al (110) as a function of temperature and within an ultrahigh vacuum environment (p < 5 × 10−12 Torr). Auger electron spectroscopy and temperature desorption spectroscopy were used to correlate the change in oxygen and carbon surface concentration. The surface oxide was observed to remain stable up to 350–400 °C. Above this temperature, the oxide began to dissociate resulting in a CO desorption peak at 425 °C followed by extensive dissolution of the C and O into the Al bulk. A second and much smaller CO desorption peak was observed at 590 °C in concert with complete oxide breakdown and the virtual disappearance of surface carbon and oxygen. Extrapolation of the Auger electron spectral ratios of CKLL and OKLL peaks to the sum of the Al0LVV and Al3+LVV peak suggests that the surface concentration of each approaches zero at ~640 °C. The predominant mechanism for reduction of the surface oxide occurs by dissolution into the bulk instead of desorption. Copyright © 2013 John Wiley & Sons, Ltd.